Pengaruh Media Pembelajaran Animasi Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPA Kelas IV SD N 1 Poncowati Kecamatan Terbanggi Besar Kabupaten Lampung Tengah: Bahasa Inggris - Vintara, Vintara; Qomario, Qomario; Nureva, Nureva (Gayaku Publisher, 2023)
Learning media is an information medium for teaching and learning activities so that it can provide effectiveness and interactivity in learning. The research objective in writing this is to determine the effect of animated media on student learning outcomes in science subjects for fourth grade students at SDN 1 Poncowati, Terbanggi Besar District, Central Lampung Regency. This study uses a type of quantitative research. With a quasi-experimental approach. The population in this study were all students of class IV B and class IV C of SDN 1 Poncowati, Terbanggi Besar District, Central Lampung Regency. The instruments used are test and non-test. using independent simple t-test hypothesis testing. This data collection technique uses observation, test and documentation methods. The results of this study indicate that the value of learning outcomes obtained after applying animation media to the experimental class has increased compared to the class that was not given treatment, namely animation media. This can be seen from the mean or average value of the experimental class, namely 79.93 with 96.6% completeness. And there is a significant influence between Animation Media on student learning outcomes. In this study researchers. This assessment results in a sig (2-tailed) value of 0.014 <0.05, which means 0.014 is smaller than 0.05. So it can be concluded that the hypothesis is accepted, namely that there is an influence of animation media on the learning outcomes of fourth grade students at SD N 1 Poncowati, Terbanggi Besar District, Central Lampung Regency.